Fetal cardiac interventions - N. Yashchuk; O. Koval; I. Ditkivskyy; B. Cherpak; I. Lukianova; Ju. Davydova; V. Lazoryshynetz (Ukrainian Journal of Cardiovascular Surgery, 2016)
Congenital heart defects are most frequent in the structure of all malformations with prevalence of 6–9 per 1,000 life newborns. CHD often are the reason of fetal and newborns deaths. Modern fetoechocardiography allows a more accurate and timely diagnosis of CHD, to clarify the pathophysiological mechanisms of their occurrence and the natural genesis. Described «mechanical» and «hemodynamic» theories of some CHD pathogenesis, the essence of which is the ability to prevent the progression of the malformations development in eliminating the etiological factor. Thus, timely effective balloon valvuloplasty stenosis of the aortic and pulmonary valves in the fetus in early pregnancy can prevent the development of hypoplastic left and right heart syndroms. The results of international research had showed that intervention in the fetus allows switch the circulation from single heart to a normal biventricular. Fetal intervention is a perspective trend in the national cardiac surgery and will improve the function of the fetus heart, the length and quality of babies life, reduce prenatal mortality.